Relevansi Kaidah Al-A’dah Muhakkamah Pernikahan dalam Islam Pada Tradisi Rompak Page di Kabupaten Lima Puluh Kota - Donna Ramadhan Fitri; Ferdi Yufriadi; Mona Eliza (IDRIS Darulfunun Institute, 2023)
One of the hallmarks of the indigenous custom of luhak Limo Puluh Kota in West Sumatra, Indonesia, is the rompak page custom. This custom involves the marriage of a couple who comes from a different area or far from the bride's nagari location. The groom by custom must deliver to the woman's family some money or gold as a sign of respect and recognition for the bride. The purpose of this study is to gain an understanding of the view of al-'adah muhakkamah (objective law) regarding the rompak page tradition in the context of the life of the indigenous community in luhak Limo Puluh Koto. This principle of Islamic law states that if a custom or action does not conflict with Islamic law and is considered clear and valid, then this custom may be preserved. In this study, researchers analyzed the views of Islamic scholars and scholars regarding the rompak page tradition in the context of al-'adah muhakkamah. In this analysis, we examined whether the rompak page tradition is following Islamic teachings or whether there are aspects that need to be adapted to the principles of Islamic law. This study has relevance and significance in understanding the suitability of the rompak page tradition with Islamic teachings in luhak Lima Puluh Kota.